Perinatal outcome in intracytoplasmic sperm injection conception versus spontaneous conception: a retrospective study - Jayakumar, Nandhini; Shankar, Kundavi; Asokan, Yamini; V., Geetha; G. V., Rashmi; Naaram, Nithya M.; K. R., Hema Niveda (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Aim of the study was to compare the perinatal outcome between intracytoplasmic sperm injection (ICSI) conception and spontaneous conception. The retrospective analysis of perinatal outcome between the ICSI conception and spontaneous conception was conducted in Institute of Reproductive Medicine, Madras Medical Mission Hospital, Chennai. Methods: All singleton babies delivered in Institute of Reproductive Medicine between January 2023 to December 2023 had been included in this study. Patient selection was done based on inclusion and exclusion criteria. All data regarding the study variables were collected from the maternal and newborn case sheets, neonatal intensive care unit (NICU) register and parturition register retrospectively and chi square test was used to analyse the statistical significance. Results: In this study, 50 spontaneous conceptions and 50 ICSI conceptions were included. The advanced maternal age (p=0.00015), gestational age at delivery (p=0.003), mode of delivery (p=0.003), birth weight (p=0.005), and Apgar score at 5 min (p=0.004) were found to be statistically significant. The incidence of intrauterine growth restriction (IUGR), NICU admissions, lower segment caesarean section (LSCS) rate, Doppler changes, and need for antenatal steroids was also found to be higher in the ICSI conception group. Conclusions: This study concluded ICSI conception is associated with higher chances of adverse perinatal morbidity in comparison with spontaneous conception. Further studies in large scale are needed to bring out the exact mechanism of these complications associated with these adverse perinatal outcomes.